Screening Endophytic Fungi for Production of Piceatannol, A Novel Inhibitor/Disruptor of α- Synuclein - Jessica (My University, 2018)
Piceatannol or trans-3,3',4,5'tetrahydroxystilbene is a natural stilbene, type of polyphenolic flavonoid whose structure is similar (except producing an extra hydroxyl group) to resveratrol. It is one of the important dietary stilbenes commonly found in red wine, berries, peanuts, grapes, and white tea. Piceatannol having high demands due to its multifarious application in neurodegenerative disorder and cardiovascular disorders. Endophytic fungi are microorganisms which colonize inside plant tissue without causing apparent harm to the host. Besides upon colonization of host plant endophytes synthesize an array of secondary metabolite which may defend the host plant against survival and stress conditions and in turn the host plant supply nutrients and habitat for endophytic fungi. Therefore in addition to interaction of endophytes with the host plant, endophyte acquires the property of their host plant and start producing analogue bioactive compounds which some have medicinal value. The current study reports the exploration of endophytic fungi isolated from Vitis vinifera for their potential to produce piceatannol. In the present study culture filtrate of endophytic fungi obtained from potato dextrose broth were screened for Biochemical assays namely: Liebermann, Chromogenic reaction and Acetic anhydride test were used for the identification of phenolic compounds, where out of 50 endophytic isolates, only 21 isolates were found to be positive among which 6 isolates were observed to show 80-90% activity and subjected to mass production. These were subsequently extracted with EA solvent and again tested for presence of piceatannol. Out of 6 isolates the EA extract of #10(B)VVLPM were found to be potent producer of piceatannol. Using TLC #10(B)VVLPM was separated to 4 bands by using solvent system, chloroform: dichloromethane in 1:1 ratio. In TLC fungal piceatannol visualized as violet color spot with symmetrical Rf 0.65 as standard. The concentration of fungal piceatannol was determined by HPLC using C18 reverse phase discovery column which exhibited symmetrical peak at RT of 6.5 min whereas the concentration of crude fungal piceatannol #10(B)VVLPM, was found to be 7.56 μg/ml. In order to confirm tentative identification, functional groups and to obtained more quantitative data FTIR and LC-MS analysis was performed. The m/z of 245.09 of #10(B)VVLPM was obtained which was similar to m/z of standard piceatannol. The fungal piceatannol producing endophytic fungi #10(B)VVLPM in our study showing strong antioxidant potential. The EA extract fungal piceatannol in DPPH assay exhibit very good scavenging activity as compared to standard piceatannol. In case of TEAC, TPC and TFC assay also same trend as in case of DPPH was obtained. The potent piceatannol producing endophytic isolates #10(B)VVLPM, was tentatively identified as Fusarium sp. The genomic DNA of the selected isolate was extracted, amplified and further send for sequencing for molecular identification.
Master of Technology- Biotechnology
Keywords: Endophytic; Fungi; Piceatannol; Fusarium sp; Grapes; α-synuclein; Parkinson’s disease